Quantifying the Backlog of Total Hip and Knee Arthroplasty Cases: Predicting the Impact of COVID-19. (November 2020) - Wilson, Jacob M.; Schwartz, Andrew M.; Farley, Kevin X.; Roberson, James R.; Bradbury, Thomas L.; Guild, George N.
Background: Total hip arthroplasty (THA) and total knee arthroplasty (TKA) are two high-volume procedures that were delayed due to COVID-19. Questions/Purposes: To help strategize an effective return to elective orthopedic surgery, we aimed to quantify the volume of THA and TKA cases delayed across the USA and estimate the time required to care for these patients when non-urgent surgery resumes. Methods: Population-level data was used to estimate monthly THA and TKA procedural volume from 2011 to 2017. Using linear regression, we used this data to project monthly procedural volumes for 2020 to 2023. Nine different permutations were modeled to account for variations in case delay rates (50%, 75%, 100%) and in resumption of non-urgent procedure timing. Two recovery pathways using the highest volume month as a surrogate for maximum operative capacity, and a second using the highest month + 20% were used to simulate a theoretical expansion of current capacity. Results: The projected national volume of delayed cases was 155, 293 (mid-March through April; 95% CI 142, 004 to 168, 580), 260, 806 (through May; 95% CI 238, 658 to 282, 952), and 372, 706 (through June; 95% CI 341, 699 to 403, 709). The best- and worst-case scenarios for delayed cases were 77, 646 (95% CI 71, 002 to 84, 290) and 372, 706 (95% CI 341, 699 to 403, 709), respectively. The projected catch-up time varied between 9 and nearly 35 months for the best- and worst-case scenarios. The addition of 20% increased productivity decreased this time to between 3.21 and 11.59 months. Conclusion: The COVID-19 pandemic has generated a significant backlog of THA and TKA procedures. Surgeons, administrators, and policymakers should account for these modeled estimates of case volume delays and projected demands.